2011
DOI: 10.2527/jas.2009-2737
|View full text |Cite
|
Sign up to set email alerts
|

Effects of choice white grease and soybean oil on growth performance, carcass characteristics, and carcass fat quality of growing-finishing pigs

Abstract: A total of 144 barrows and gilts (initial BW = 44 kg) were used in an 82-d experiment to evaluate the effects of dietary fat source and duration of feeding fat on growth performance, carcass characteristics, and carcass fat quality. Dietary treatments were a corn-soybean meal control diet with no added fat and a 2 × 4 factorial arrangement of treatments with 5% choice white grease (CWG) or soybean oil (SBO) fed from d 0 to 26, 54, 68, or 82. At the conclusion of the study (d 82), pigs were slaughtered, carcass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
42
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 32 publications
(33 reference statements)
13
42
1
2
Order By: Relevance
“…Numerous studies have shown that adding fat to swine diets in some or all of the finishing phase im proves feed efficiency when compared with pigs fed a diet without fat (Weber et al, 2006;Benz et al, 2011a;Kellner et al, 2014). The increase in ADG from d 0 to 42 for pigs fed added fat in the current study agrees with (Continued) results from Campbell and Taverner (1988) and De la Llata et al (2001), indicating pigs were in an energy dependent state for this period of growth as described by Pettigrew and Esnaola (2001).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Numerous studies have shown that adding fat to swine diets in some or all of the finishing phase im proves feed efficiency when compared with pigs fed a diet without fat (Weber et al, 2006;Benz et al, 2011a;Kellner et al, 2014). The increase in ADG from d 0 to 42 for pigs fed added fat in the current study agrees with (Continued) results from Campbell and Taverner (1988) and De la Llata et al (2001), indicating pigs were in an energy dependent state for this period of growth as described by Pettigrew and Esnaola (2001).…”
Section: Discussionsupporting
confidence: 82%
“…However, a 40 and 19d withdrawal still maintained a difference of 5.5 and 6.4 percentage units for C18:2 as well as 5.5 and 8.7 g/100 g, respectively, for jowl fat when compared with pigs not fed a diet with added fat. Benz et al (2011a) also reported that with an extended withdrawal period, a greater reduction in C18:2, PUFA, and IV can be observed in backfat and jowl fat when feeding 5% soybean oil. We observed similar responses in backfat as a 42d withdrawal from pigs previously fed a 4% soybean oil diet resulted in 6.94 and 8.13 per centage units decrease in C18:2 and PUFA, respective ly, and also lowered IV by 11.55 g/100 g for backfat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the backfat of both groups the PUFA n-6/n-3 ratio amounted to 1.7, whereas in the control group it was 5.56 (Grześkowiak 1 diets: A = 2.5% rapeseed oil and 1% linseed oil, B = 1% rapeseed oil, 2% fish oil + 0.5% lard, C = 2.5% linseed oil and 1% fish oil, D = 2.3% linseed oil, 1% rapeseed oil + 0.2% lard 2 all saturated fatty acids 3 all monounsaturated fatty acids 4 all polyunsaturated fatty acids 5 dietary fatty acids having undesirable hypercholesterolemic effect in humans (C14:0 + C16:0) 6 ΣPUFA + MUFA 7 dietary fatty acids having desirable neutral of hypocholesterolemic effect in humans (UFA + C18:0) X-Z different letters within a row indicate significant differences P ≤ 0.01 (*P < 0.05) x-z different letters within a row indicate significant differences P ≤ 0.05 (**P < 0.01) ns = nonsignificant difference Benz et al (2011) used in the diet a 5% supplement of soybean oil in a period of 25 to 82 days of the pigs' life. In the backfat of animals, the total content of PUFA acids increased from 17.2% (on day 26 of feeding) to 29.6% (on day 82).…”
Section: Fatty Acids Composition (%) Of Backfat Lipidsmentioning
confidence: 99%
“…Worse results in the modification of the fatty acids profile were stated in the case when olive oil (Nuernberg et al, 2005) or soybean oil (Benz et al, 2011) was used. According to Mitsumoto et al (1991) and Leksanich et al (1997), too high amount of polyunsaturated fatty acids in the intramuscular and depot fat affects the fat consistency (soft, sticky), worsens the taste, and also durability.…”
mentioning
confidence: 99%